Peralihan dan Regenerasi Pengetahuan Beserta Skema Kebijakan Retensi Etnobotani Pewarna Alami pada Masyarakat Blok Kebon Gedang Cirebon - Muhammad Abdul Jabar; Iryani, Riris; Nadifa, Jasmine Augi; Widiatningrum, Talitha (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Kebon Gedang Block is one of the few areas of natural dye batik craftsmen in Indonesia. The activity of using natural dyes for batik has been carried out from generation to generation. This study aims to analyze the transfer of ethnobotanical knowledge of natural dyes based on age class (KU), analyze ways to regenerate and analyze the policy scheme for retention of ethnobotanical knowledge of natural dyes in the Kebon Gedang Block. The main methods used in this study were semi-open interviews, observation, and documentation. The selection of respondents was carried out by purposive sampling by considering age (years), namely I (30-39), II (40-49), III (50-59), IV (> 60). The results showed that the level of knowledge of natural dyes and retention was highest in KU III because the people were still healthy, strong, and generally still actively following the development of the batik industry. However, KU III is the group with the highest change in knowledge and is feared to be lost. While at other KU levels, the inheritance of knowledge is still going well. The policy of retaining ethnobotanical knowledge of natural dyes can be carried out in several ways, including by creating books, booklet or electronic sites about knowledge of natural dyes, as well as by registering intellectual property rights. This research can record the current state of knowledge so that efforts can be made to avoid losing this knowledge.